The rational legislation as a scientific paradigm - Kantor-Kozdrowicki, Piotr (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
The article compares the presumption of rational legislation with the concept of scientific paradigm. Individual features of rational legislation thesis, as its idealization model, counterfactuality and non-empiricalness meet the features of science paradigm as described by T.S. Kuhn. An analyzis of this assumption demonstrates that the paradigm of rational legislation (and rational legislator) is the basic assertion of Polish jurisprudence as science, both in its theoretical and practical meanings. The study cites arguments critical of the concept of rational legislation; however, it proves that they do not lead to overthrowing the paradigm; furthermore, they confirm scientificity of Polish jurisprudence as a mature and growing discipline of knowledge.
Keywords: rational legislation; rational legislator; paradigm; T.S. Kuhn